A study of serum C peptide levels in newly detected diabetic patients in tertiary care hospital - Teli, Balakrishna; S., Prabhu; Biradar, Sneha (International Journal of Advances in Medicine, 2021)
Background: Diabetes mellitus (DM) refers to a group of common metabolic disorders that share the phenotype of hyperglycemia. The deficiency of C-peptide in type 1 DM or its excess in type 2 DM leads to the development of disorders which includes the cardiovascular, nervous, excretory and other systems. The present study is done to assess the serum C-peptide levels in newly detected diabetic patients and its significance in classification of diabetes and deciding about management. Methods: This cross sectional study was conducted within the hospitals attached to Bangalore medical college and research institute. 65 newly detected diabetes patients who gave consent for study and satisfy the inclusion criteria were included in the study. Data was collected using semi structured questionnaire, clinical examination and relevant investigations. Statistical analysis was performed using SPSS software. A p value of <0.05 was considered significant. Results: C-peptide levels showed that 34 (52.3%) subjects had C-peptide levels >2 followed by 10 (15.4%) subjects having 0.1 to 0.6, 9 (13.8%) subjects having 1 to 2, 6 (9.2%) subjects each having 0.6 to 1 and <0.1. Conclusions: Serum C-peptide levels are useful as an index of endogenous insulin production. Low C-peptide levels need insulin treatment due to poor insulin reserve. Majority of the subjects, who had low serum C-peptide levels also had low BMI suggesting a positive correlation between C-peptide levels and BMI.